CONCEPT OF BUILDING AND USING THE DIGITAL KNOWLEDGE PLATFORM ON THE SPECIALTY - Константин Александрович Метешкин (Радіоелектронні і комп'ютерні системи, 2019)
The paper proposed the concept of building and using the digital knowledge platform on the specialty. Experimental methods, together with the method of simulation, ensure the reliability of the obtained theoretical results and give confidence in the creation and use of digital knowledge platforms in specific specialties at the main departments. The digital knowledge platform is a special way organized and interconnected models of educational disciplines, which isomorphically reflect the content of the curriculum training programs. The partial implementation and experience of using the digital knowledge platform in individual disciplines have shown that the creation and maintenance of such platforms require certain resource costs. At the same time, the transition to an innovative training technology based on digital knowledge platforms will make it possible to move away from the traditional anthropocentric training model to a more progressive system-synergetic model that takes into account the capabilities of modern information technologies. The results of experimental studies conducted to clarify the possibility of students to create models of their knowledge showed that students are able to create models of their knowledge, which can be taken as a basis for the formation of a generalized model of training knowledge, which is the main element of digital knowledge platforms. In addition, within the framework of the concept being developed, another new term “plite” was introduced, the semantic part of which denotes a knowledge platform for the specialty. The technology of creating the plites should obviously be similar to the technology of creating the sites, and the peculiarity should be that their structures were isomorphic to the structures of curriculum, and the content part should be used exclusively for teaching. Then, fully developed plites for specific specialties will be independent units of educational knowledge that can be used for educational purposes by other higher educational institutions.